Characteristics and trends of childhood cancer in Pudong, China, 2002-2015 - Junqi Ji; Zheng Luo; Yichen Chen; Xiaoyun Xu; Xiaopan Li; Shijian Liu; Shilu Tong (BMC, 2020)
Abstract Background With the growing threat of cancer to children's health, it is necessary to analyze characteristics and trends of childhood cancer to formulate better cancer prevention strategies. Methods Data on the 430 children with cancer during 2002-2015 were collected from the Pudong Cancer Registry, diagnosed with the International Classification of Diseases for Oncology and categorized according to the International Classification of Childhood Cancer. The incidence rate, trends over time, and survival of patients grouped by sex, age, and region were explored using the Kaplan-Meier, Cox regression, and Joinpoint Regression models. Results The crude childhood cancer incidence and world age-standardized incidence rate (ASR) were 115.1/1,000,000 and 116.3/1,000,000 person-years. The two most frequent cancers were leukemia (136/430, 31.63%, ASR, 37.8/1,000,000 person-years) and central nervous system (CNS) tumors (86/430, 20.00%, ASR, 22.9/1,000,000 person-years). Our findings indicate that the survival rate for children between 10 and 15 years of age was higher than that for 5-10; and the survival rate for children who had leukemia was higher than that of children with CNS tumors. However, the overall incidence of childhood cancer, and leukemia, CNS tumors remained relatively stable in Pudong between 2002 and 2015. Conclusions The incidence and survival rate for childhood cancer patients varied by age and cancer type. The overall trends of childhood cancer incidence remained relatively stable in Pudong from 2002 to 2015 even though socioeconomic development has been unprecedentedly fast in this region.